In situ synthesis of TiB2 particulate reinforced copper matrix composite with a rotating magnetic field. (January 2015) - Wang, Tongmin; Zou, Cunlei; Chen, Zongning; Li, Mingyu; Wang, Wei; Li, Rengeng; Kang, Huijun
Highlights: TiB2 /Cu composites were in-situ synthesized by casting Cu–Ti and Cu–B alloys. Rotating magnetic field was introduced into the solidification of the composites. The effect of RMF on the distribution of TiB2 particles was analyzed. The relationships among RMF, TiB2 distribution and properties were investigated. Abstract: In situ TiB2 particulate reinforced copper matrix composites were prepared using Cu–Ti and Cu–B master alloys. Rotating magnetic field (RMF) was employed to improve the dispersion of in situ TiB2 particles during casting. The influences of RMF on the microstructures, TiB2 distribution and mechanical properties of thus prepared composites were investigated. The results show an improved distribution of TiB2 particles in the copper matrix, which resulted in the improvement of mechanical properties of Cu/TiB2 composites. The ultimate tensile strength and Vickers hardness of Cu–1 wt.% TiB2 with a 30% reduction hot rolling and a 90% reduction cool rolling increased from 405 MPa, 125 HV to 470 MPa, 171 HV by the variation of field currents, respectively. Moreover, the action mechanism of RMF on TiB2 distribution in the copper matrix was explained and analyzed.